Breaking The Spell of Tax Budget Magic - Perkins, Rachelle Holmes (Columbia Journal of Tax Law, 2015)
To date, tax scholars have responded to the proliferation of so-called temporary or sunset tax expenditure legislation by staking claims either for or against it, focusing on its relative merits and shortcomings. In this Article, I argue that these positions are analytically incomplete. Rather than address the underlying deficiencies in the budget process that have led to the preference for temporary tax provisions, the advocacy of the use (or non-use) of temporary provisions simply asks which type of provision will yield the least problematic results. This Article seeks to help fill a gap in the literature by focusing on remedies meant to address the source of many issues related to both temporary and permanent tax expenditure legislation. In particular, I propose the adoption of a bundle of new budget rules that will work as precommitment devices to restrain lawmakers from exploiting weaknesses in the existing process. I argue that these proposed rules would still give lawmakers the flexibility to adopt either temporary or permanent tax legislation as appropriate. However, the proposed rules would help to decrease opportunities for budget manipulations, impose more fiscal restraint on lawmakers, achieve greater legislative transparency, help loosen the hold of special interest groups on lawmakers, and enhance legislative stability.